Maude Horton's glorious revenge - Pook, Lizzie (Simon & Schuster, 2024)
"In Victorian London, when she discovers her sister's death aboard the Makepeace was no accident and that the ship's scientist Edison Stowe was responsible, Maude Horton, to find the truth, begins shadowing Edison, enacting the ultimate revenge to get justice for her sister"--